INVESTIGATION OF FEEDING ROLLERS ALIGNMENT IN A HORIZONTAL PLANE - Tarasova, Ol'ga; Chernova, Mariia (Journal of Applied Engineering Science, 2017)
This research represents the ways of estimation of woodworking machines’ feed rollers arrangement in a horizontal plane as exemplified by control of the position of the feed rollers axes on a frame saw. Some significant considerations have been stated in relation to standard methods of control GOST 10294, which contain accuracy value and monitoring techniques. Some methods are recommended in the following research, which allow monitoring value of possible deviations of mutual arrangement of feed rollers in a horizontal plane. This is done with due consideration of inaccuracy of their setting, as well as radial beats that results from exploitation, by means of conducting measurements in two mutually perpendicular planes.
Keywords: setting inaccuracy; feeding rollers; axes alignment; arrangement accuracy